Please solve this. I will mark as the brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d5b/bf9533715b65cb5cf783e936b3b6b379.jpg)
Answers
Answered by
1
Answer:
Hello , I hope it will help you~
Step-by-step explanation:
tan θ = a/b
sinθ/cosθ = a/b------(1)
lhs = (a sinθ- b cos θ)/(a sinθ + b cosθ)
= (asinθ/cosθ - bcosθ/cosθ)/(asinθ/cosθ+ bcosθ/cosθ)
dividing each term with cosθ
=(asinθ/cosθ-b/1)/(asinθ/cosθ+b/1)
=(a*a/b-b/1)/(a*a/b +b/1)
[from (1)]
= (a^2-b^2)/(a^2+b^2)
=rhs
Mark as brainleast
Similar questions